ANALISIS YURIDIS TERHADAP HAK DAN KEWAJIBAN PEKERJA BERDASARKAN UNDANG-UNDANG KETENAGAKERJAAN - Sandy Wiratno H Simanjuntak (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to provide a juridical analysis of workers’ rights and obligations based on labor law in Indonesia. The focus of the study lies in the normative regulation governing employment relationships between workers and employers. The research employs a normative legal approach using primary, secondary, and tertiary legal materials. The analysis is conducted qualitatively through interpretation of relevant statutory provisions. The results indicate that labor law in Indonesia has established a comprehensive framework regulating workers’ rights, including fair wages, social security, occupational safety, and freedom of association. Workers’ obligations are also clearly defined through provisions related to job performance, compliance with company regulations, and responsibility toward company interests. The main issue is found in the implementation aspect, where a gap exists between legal norms and practical conditions. Contributing factors include low legal awareness, weak supervision, and the increasing complexity of modern employment systems. The study concludes that the Indonesian labor law system has a strong normative foundation. Improvements are required in law enforcement, legal awareness, and regulatory reform to address contemporary labor challenges.